Diagnosis and treatment of a penetrating brain injury caused by a welding electrode: A case report. Issue 10 (March 2019) - Shi, Lin; Sun, Yue; Chen, Limin; Xue, Hang; Zhang, Weitao; Yang, Hongfa
Abstract: Rationale: Penetrating brain injury caused by a welding electrode is a rare occurrence. This type of injury requires careful preoperative assessment and timely treatment measures to avoid secondary damage. Patient concerns: A 55-year-old male patient fell from a height of approximately 5 m during when a welding electrode in his left hand was inadvertently inserted into his brain. The patient had a GCS score of 15 and complaints of dizziness and headache. CT showed an object of metallic density penetrating the skull and entering the brain parenchyma in the frontotemporal region. Diagnosis: According to the clinical findings and preoperative imaging examination, the diagnosis was open craniocerebral injury with intracranial foreign body and left orbital wall fracture. Intervention: After definite diagnosis and sufficient preoperative preparation, active surgical treatment was carried out to remove intracranial foreign body. Anti-infection and other symptomatic treatment were given after operation. The signs of infection and changes of vital signs were closely observed. Outcomes: After treatment, no obvious adverse reactions were found and the patient was discharged. No complications such as infection occurred during the follow-up period of 6 months. Lessons: In treating patient with a welding electrode penetrating the brain, assessments need to be made preoperatively, the welding electrode needs to be removed in a timely manner, complete hemostasis needs to be achieved during surgery with total repair of the damaged area, and anti-inflammatory treatment needs to be administered postoperatively to achieve good results.